Luka Bakar - Mohd Reza Bahlia; M Bayu Rizaldy (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Burns are a type of trauma caused by various external factors such as heat, electrical current, chemicals, or lightning, which can damage the skin, mucosa, and deeper tissues. Extensive burns can affect the metabolism and overall function of the body. Burns are classified based on their severity: first-degree burns (affecting only the epidermis with symptoms of erythema and pain), superficial second-degree burns (extending into the epidermis and part of the dermis, accompanied by blisters and severe pain), deep second-degree burns (involving the entire dermis), and third-degree burns (involving the epidermis, dermis, and subcutaneous tissue, with damage to blood vessels that reduces blood flow to the affected area). Burn management aims to prevent infection and allow epithelial cells to proliferate and close the wound. Additionally, burns can lead to serious complications such as hypovolemic shock, pneumonia, urinary tract infections, cellulitis, and skin contractures. Therefore, prompt and proper initial treatment is crucial to prevent further complications. With a better understanding of burns, it is hoped that the quality of patient care can be improved, accelerating the healing process and reducing the risk of serious complications.